Dimensions of protection behaviors: A systematic literature review - Al-Harthy I.M.; Rahim F.A.; Ali N.; Singun A.P.; JR (Little Lion Scientific, 2023)
The term Bring Your Own Device (BYOD) has generated many hopes and fears among many users in this field related to behaviors of information protection. Threats of BYOD include illegal access to policy changes and information, disclosure of confidential details to the public, leakage of organization data and privacy, access control, abuse, and lost of devices. This study examines the existing studies on various dimensions in conceptualizing the behaviors of information protection. Using a systematic method, we analyzed four major databases, including IEEE, Science Direct, SpringerLink, and Taylor & Francis, from which 57 articles were selected from the year 2010 to 2019. In this study, ten (10) dimensions are discussed: protection behaviors and its Perceived Severity, Perceived Vulnerability, Self-Efficacy, Response Efficacy, Response Cost, Subjective Norm, Attitude, Security Self-Efficacy, Information Security Awareness and Perceived Behavioral Control. 2005 ongoing JATIT & LLS.